Dynamic High-Cadence Cycling Improves Motor Symptoms in Parkinson’s Disease - Ridgel, Angela L.; Phillips, Robert S.; Walter, Benjamin L.; Discenzo, Fred M.; Loparo, Kenneth A. (Frontiers in Neurology, 2015)
Rationale Individuals with Parkinson’s disease (PD) often have deficits in kinesthesia. There is a need for rehabilitation interventions that improve these kinesthetic deficits. Forced (tandem) cycling at a high cadence improves motor function. However, tandem cycling is difficult to implement in a rehabilitation setting. Objective To construct an instrumented, motored cycle and to examine if high cadence dynamic cycling promotes improvements in motor function. Method This motored cycle had two different modes: dynamic and static cycling. In dynamic mode, the motor maintained 75–85 rpm. In static mode, the rider determined the pedaling cadence. UPDRS Motor III and Timed Up and Go (TUG) were used to assess changes in motor function after three cycling sessions. Results Individuals in the static group showed a lower cadence but a higher power, torque and heart rate than the dynamic group. UPDRS score showed a significant 13.9% improvement in the dynamic group and only a 0.9% improvement in the static group. There was also a 16.5% improvement in TUG time in the dynamic group but only an 8% improvement in the static group. Conclusion These findings show that dynamic cycling can improve PD motor function and that activation of proprioceptors with a high cadence but variable pattern may be important for motor improvements in PD.